Protein Tyrosine Phosphatase Receptor S Acts as a Metastatic Suppressor in Malignant Peripheral Nerve Sheath Tumor via Profilin 1-Induced Epithelial-Mesenchymal Transition - Ren, Jie-Yi; Gu, Yi-Hui; Cui, Xi-Wei; Long, Man-Mei; Wang, Wei; Wei, Cheng-Jiang; Gu, Bin; Zhang, Hai-Bing; Li, Qing-Feng; Wang, Zhi-Chao (Frontiers in Cell and Developmental Biology, 2020)
Malignant peripheral nerve sheath tumors (MPNST) are aggressive sarcomas with over half of cases developed in the context of neurofibromatosis type 1. Surgical resection is the only effective therapy for MPNST. The prognosis is very dismal once recurrence or metastasis occurs. Epithelial-mesenchymal transition (EMT) is a key process of recurrence and metastasis involving reorganizations of the actin cytoskeleton and actin-binding proteins (ABP) play a non-negligible role. Protein tyrosine phosphatase receptor S (PTPRS), a tumor suppressor previously reported in colorectal cancer, hepatocellular carcinoma and head and neck cancer, is thought to mediate cell migration and invasion by downregulation of EMT. However, its role in MPNST remains unknown. In the present study, by using tissue microarray we demonstrated low expression of PTPRS was related to poor prognosis in MPNST. Knockdown of PTPRS in MPNST cell lines increased migration/invasion and EMT processes were induced with increased N-cadherin and decreased E-cadherin, which indicated PTPRS may serve as a tumor suppressor in MPNST. In addition, we tested all EMT related ABP and found profilin 1 was significantly elevated in PTPRS downregulated MPNST cell lines. As a member of actin-binding proteins, profilins are regulators of actin polymerization and contribute to cell motility and invasion, which have been reported to be responsible for EMT. Moreover, results showed that downregulation of profilin 1 could restore the EMT processes caused by PTPRS downregulation in vitro and in vivo. Furthermore, high expression of profilin 1 was significantly associated with dismal prognosis. These results highlighted PTPRS served as a potential tumor suppressor in the recurrence and metastasis of MPNST via profilin 1 induced EMT processes and it might provide potential targets for future clinical therapeutics.